2008
DOI: 10.1111/j.1467-8276.2007.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Stamp Program Participation and Food Insecurity: An Instrumental Variables Approach

Abstract: The relationship between Food Stamp Program (FSP) participation and household food insecurity (FI) is investigated using data from the 1996–1997 National Food Stamp Program Survey. Endogeneity of FSP participation is accommodated with an instrumental variables approach. In contrast to other findings reported in the literature, results suggest participation in the FSP reduces the severity of FI. Sociodemographic variables play important roles in FSP participation and FI. Underreporting of FSP participation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 15 publications
7
104
1
Order By: Relevance
“…Further studies might therefore investigate the effects of WIC, SNAP and other food assistance programs on outcomes besides nutrient intakes, such as diet quality, overweight, and obesity. The modeling approach developed in this study emphasizes the often-ignored sample selectivity in multiple program participation in a multi-outcome framework and should be of use in the investigation of other programs and diet and health outcomes, such as pregnancy and birth outcomes (Bitler and Currie, 2005) and food insecurity Yen et al, 2008). Finally, the econometric model developed in this study relies on the multivariate normality assumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies might therefore investigate the effects of WIC, SNAP and other food assistance programs on outcomes besides nutrient intakes, such as diet quality, overweight, and obesity. The modeling approach developed in this study emphasizes the often-ignored sample selectivity in multiple program participation in a multi-outcome framework and should be of use in the investigation of other programs and diet and health outcomes, such as pregnancy and birth outcomes (Bitler and Currie, 2005) and food insecurity Yen et al, 2008). Finally, the econometric model developed in this study relies on the multivariate normality assumption.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have investigated the role of SNAP in household food insecurity (Yen et al, 2008) obesity and health care spending (Chen et al, 2005;Meyerhoefer and Pylypchuk, 2008), and the role of WIC in nutritional risk , pregnancy, and birth outcomes (Bitler and Currie, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is meant to support lowincome households in consumption of a healthy, nutritious diet. While there is some evidence that first of these goals is being accomplished Yen et al (2008), DePolt et al (2009), Ratcliffe et al (2011), Shaefer and Gutierrez (2012), evidence on the second is more mixed; for example, a recent study found that SNAP participation increases consumption of whole fruit, but leads to a small decrease in consumption of dark green and orange vegetables . Many other studies have yielded similar inconclusive results.…”
Section: Introductionmentioning
confidence: 99%
“…Public assistance programs continue to be an important safety net for low-income households in the US. Research has found SNAP, in particular, is effective in reducing food insecurity [18,19]. As Coleman-Jensen et al (2013) note, "Food and nutrition assistance programs of the U.S. Department of Agriculture (USDA) increase food security by providing low-income households access to food, a healthful diet, and nutrition education" ( [20], p. 7).…”
Section: The History and Importance Of Public And Charitable Assistanmentioning
confidence: 99%